Preparation of tetrafluoro-λ6-sulfanyl bridged-bonding perfluoroalkyl phenylethyltrichlorosilane and its application on fabric finishing. (22nd July 2020) - Chang, Guangtao; Chen, Lei; Li, Zhanxiong
Abstract: In this study, one novel perfluoroalkyl silane with tetrafluoro- λ 6 -sulfanyl bridging group named 4-(Tridecafluorohexyl sulfur tetrafluoride) Phenylethyl trichlorosilane (PFSTS) was successfully synthesized via fluorination and hydrosilylation. The structure was characterized by FT-IR and NMR Then, the product and the control subject 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane (PFOTS) were finished onto PET fabrics through the method of dip-and-pad. The wettabilities of the treated PET fabrics were characterized by Water Contact Angles (WCA) and surface free energies measurements. X-ray Photo electron Spectroscopy (XPS) was used to validate the attachment, together with the chemical composition of the polymers on the surface of treated PET fabrics. The WCAs of PFOTS@PET and PFSTS@PET were 142.2°, 137.3°, while the WCA of untreated PET fabrics is 120° in general, indicating that PFTOS and PFSTS can provide good hydrophobicity by finishing PET fabrics. After the 48 h exposure to accelerated agingUV irradiation, sample of PFSTS@PET show a decreased CA value by 12.5% from 137.3° to 120.1°, while for sample of PFOTS@PET, the percentage of reductionis only 2.8%. It was found that the perfluoroalkyl trichlorosilane that containing –SF4 – bridged group exhibited excellent water-repellency properties and had higher potential to UV degrade as possessing weak bond energy of C–S bond, so the PFSTS might act as an eco-friendly alternative to carbon-chain perfluoroalkyl derivatives in water-repellency areas.